2016
DOI: 10.1016/j.jand.2016.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of 24-Hour Dietary Recalls as a Measure of Diet in African-American Youth

Abstract: Background Although it is a common practice to estimate dietary intake using three random 24-hour dietary recalls, some studies have suggested up to nine may be necessary to reliably estimate usual intake in youth. Given the resulting increase in resources and participant burden, more research is needed to determine if this method is reliable, particularly in African American youth at increased risk for obesity and other chronic diseases. Objective This study estimated the reliability with which 24-hour diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 39 publications
0
27
0
1
Order By: Relevance
“…Some limitations of the present study should be considered. First, recall bias was inevitable because of the use of a diet history interview and its questionable reliability (40). Second, under-reporting, a common limitation based on history dietary assessment, could lead to measurement bias.…”
Section: Discussionmentioning
confidence: 99%
“…Some limitations of the present study should be considered. First, recall bias was inevitable because of the use of a diet history interview and its questionable reliability (40). Second, under-reporting, a common limitation based on history dietary assessment, could lead to measurement bias.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, considering that more times we interviewed, less cooperate would TB patients be because they may be worried about being discriminated against, so we took the 2-day 24hdrs method instead of the commonly used 3-day 24hdrs, but the reliability may decrease. A study conducted among African American youth showed that reliability estimates for 3-day 24hdrs ranged from 27%-62%, while, for 2-day 24hdrs, it ranged from 19%-52% [39]. And, when measuring the consumption of condiments, we didn't take the household weighing method commonly used in nutrition survey.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Although facilitation strategies are provided to encourage accurate and complete recall, a research study suggests that 24-hour diet recall in children results in low reliability due to both variations in diet across days and inaccuracy in reporting (George, Van Horn, Lawman, & Wilson, 2016). Next, the current survey format does not include audio instructions.…”
Section: Limitationsmentioning
confidence: 99%